Thailand Ranat Xylophone: Analysis of the Musical Scale System - Ahmad F., Musib; Sinin, Hamdan; Khairul Anwar, Mohamad Said; Aaliyawani E., Sinin (NC State University, 2025)
The ranat ek belongs to the percussion family. It consists of wooden bars suspended by cords above a boat-shaped trough resonator and is played with two mallets. Serving as the principal instrument in the Thai Piphat ensemble, the ranat ek holds both musical and cultural significance in traditional Thai performance. This study examined its acoustic and tuning characteristics using modern signal analysis tools to contribute to audio preservation and future instrument design. The sound signals were recorded in real time using a PicoScope 3000. The notes identified for bars 1 to 17 ranged from C5 to E7. Grouped by octaves, octave 5 includes C5-A♯5, octave 6 includes C6-B6, and octave 7 includes C7-E7. The analysis revealed a non-tempered, heptatonic tuning system distinct from the Western equal temperament scale, reflecting the ranat ek’s unique cultural tuning identity. The note distribution across octaves confirmed a scale structure emphasizing natural harmonic overtones rather than fixed semitone intervals. These findings establish a scientific foundation for digital sound preservation and provide baseline data for AI-assisted sound modeling and immersive AR/VR applications in cultural heritage reconstruction. The study suggests that the collected data could inform sustainable instrument design using plant-based materials, supporting both cultural continuity and ecological innovation.